An Approach toward 17-Arylsubstituted Marginatafuran-Type Isospongian Diterpenoids via a Palladium-Catalyzed Heck–Suzuki Cascade Reaction of 16-Bromolambertianic Acid - Yurii V. Kharitonov; Elvira E. Shults (Molecules, 2022)
Isospongian diterpenes are a small but growing family of natural tetracyclic secondary metabolites isolated from marine organisms, primarily sponges and nudibranchs. A palladium-catalyzed domino Heck–Suzuki reaction sequence for the synthesis of the tetracyclic skeleton of marginatafuran-type isospongian diterpenoids with a wide variety of substituents in the C-17 position is reported. The proposed approach was based on selective transformations of the accessible plant diterpenoid lambertianic acid and includes an intramolecular Heck reaction of 16-bromolambertianic and arylation of the palladium intermediate with arylboronic acid. The influence of the nature of the substituent both in arylboronic acids and in the furan ring of 16-bromolambertianic acid on the direction and chemoselectivity of the reaction has been studied. The described derivatization of natural furanolabdanoid lambertianic acid produced new functionalized molecules for biological study and gave novel insights into the reactivity of complex molecular structures.